Inadvertent laparoelytrotomy in second stage of labour: a case report - Mohanty, Shristy; Marandi, Satyabhama; Chhatria, Bhismadev (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Laparoelytrotomy is the accidental delivery via a vaginal incision during caesarean section in second stage of labour. It refers to the inadvertent delivery of the foetus through a transverse incision given over the vagina during a caesarean section (C-section). It is a rather uncommon complication of C-section encountered at advanced dilation which can lead to maternal complications such as traumatic postpartum hemorrhage, injury to bladder, ureters and difficult reconstruction of vagina. Here, we present a case report of inadvertent laparoelytrotomy during C-section.